Emerging churches creating Christian community in postmodern cultures - Gibbs, Eddie; Bolger, Ryan K. 1963- (Grand Rapids, MI Baker Academic, 2006)
Contents : A brief look at culture -- What is the emerging church? -- Identifying with Jesus -- Transforming secular space -- Living as community -- Welcoming the stranger -- Serving with generosity -- Participating as producers -- Creating as created beings -- Leading as a body -- Merging as ancient and contemporary spiritualities -- Conclusion -- Appendix 1 : Leaders in their own words -- Appendix 2 : Research methodology. Includes bibliographical references and index.
Keywords: Church renewal; Church growth; Community -- religious aspects -- Christianity